Nilai-Nilai Pendidikan Dalam Al-Quran Surah Al-Jum’ah Ayat 2 - M. Khoir Al Kusyairi; Husni Fuaddi (EL-EMIR Institute, 2025)
Islamic education is a collection of interrelated life principles that contain teachings to maintain and develop human nature and human resources that exist in it towards the formation of a complete human being (insan kamil) in accordance with Islamic teachings. This article aims to determine the educational values ​​​​in the Qur'an, Surah Al-Jumu'ah, verse 2. The research method used is a qualitative method with a type of library research that involves searching for information in books and articles with topics related to this research. The results of this study based on the results of the analysis and discussion, it can be concluded that the educational values ​​​​contained in Qs. Al-Jumu'ah verse 2, namely that in this verse the task of the Messenger or the task of his heirs (educators) is to read the verses of Allah SWT. Most commentators interpret this verse with the Qur'an as a whole, some limit the verses of the Qur'an that contain the kauniyah verses that show the Qudrah of Allah SWT, the wisdom and the oneness of Allah SWT. There are also those who explicitly mention the Kauniyah verses that span the universe. Reading it means teaching monotheism through natural phenomena that unfold in this universe. Then teaching the Bible (the content of the Koran) and al-hikmah is done in an integral manner.